Infinitive Forms and Conditional Mood of Verbs as a Means of Expressing a Concretizing Relation - Sagdieva, Ramilya Kamilovna; Husnutdinov, Damir Haydarovich; Mirzagitov, Ramil Hamitovich; Abikenova, Gulnat Tokenovna (International Journal of Criminology and Sociology, 2022)
A concretizing link is an expression of a specific relationship between concepts using a unique means of relation. Given that, affixes and forms of verbs have a particular place. This article considers the conditions of the infinitive (-ырга/-ергә/-рга) and the conditional mood of the verb (-са/-сә). These affixes in Tatar grammars as part of a subordinate predicate clause are inflectional forms, that is, linking words. The authors study these verb forms to express a concretizing relation and analyze the shades of meanings. A more profound analysis shows that these affixes express different relations between phenomena and connect the verb with other words. They are added to all the verbs and some parts of speech when in speaking. It must be said that the affixes of the conditional mood and, to some extent, the infinitive perform the same functions for the verb as the cases do for the noun. The primary research method is descriptive-analytical with its main components: observation, generalization, and interpretation. For a detailed analysis of the linguistic features of speech, a comparative historical method is also used, which allows for the determination of some tendencies in the development of the grammatical system of the national literary language. In the studies, comparative-typological and statistical methods are also applied.